An Interesting Final-Year Undergraduate Laboratory Project: Investigation of Gypsum Scale Formation on Piping Surfaces - S. Muryanto; H M Ang (Department of Chemical Engineering, Universitas Gadjah Mada, 2005)
The formation of scales in pipes and on the surfaces of vessels is one of the major problems encountered by the mineral processing industry in Australia and elsewhere. A cursory study revealed that one of the main components of the scales was gypsum or calcium sulfate dihydrate. This paper discusses a typical undergraduate laboratory project to investigate the formation of calcium sulfate dihydrate scale on the surfaces of different types of pipes under isothermal conditions. This laboratory exercise is essentially a crystallization process and is suggested as one of the topics for final-year chemical engineering undergraduate project since it is a very important unit operation in the chemical, mineral, or pharmaceutical industries. Keywords: Calcium sulfate dihydrate, laboratory project, scale formation, and undergraduate curriculum..